WORK ETHIC OF NYAO PEOPLE IN MOSSO VILLAGE, INDONESIA AND PAPUA NEW GUINEA (PNG) BORDER AREA - Frank, Simon Abdi Kari; Idris, Usman; Flassy, Marlina; Ilham, Ilham; Abisay, Andi; Indiarti, Nona Riri; Darmawan, Hironimus (Transpublika Publisher, 2024)
This research aims to understand the work ethic of the Nyao people in Mosso Village, a border area between Indonesia and Papua New Guinea (PNG). The research focuses on identifying the factors that shape their work ethic and its impact on social, economic and cultural life. A qualitative approach was used in this research with ethnographic methods. Data was collected through in-depth interviews with key informants selected using a snowball sampling technique, including village heads, traditional leaders (Ondoafi), and community members. Participatory observations were also conducted to understand community work practices firsthand. Data analysis was conducted inductively through the stages of coding, categorization, and interpretation. The results showed that the work ethic of the Nyao community was formed since childhood through the socialization of cultural values in the family and community. The main factors that drive their work ethic include the values of honesty, discipline, responsibility, and adaptation to the environment. In addition, interaction with the surrounding community and the desire to achieve a better life also strengthen their work motivation. This work ethic contributes to household economic sustainability and maintaining social harmony within the community.